Echocardiographic Evidence of Early Diastolic Dysfunction in Asymptomatic Children with Osteogenesis Imperfecta - Khalfan S. Al-Senaidi; Irfan Ullah; Hashim Javad; Murtadha Al-Khabori; Saif Al-Yaarubi (Sultan Qaboos University Medical Journal, 2015)
Objectives: Structural and functional cardiovascular abnormalities have been reported in adults with osteogenesis imperfecta (OI); however, there is a lack of paediatric literature on this topic. This study aimed to investigate cardiovascular abnormalities in children with OI in comparison to a control group. Methods: This case-control study was conducted at the Sultan Qaboos University Hospital in Muscat, Oman, between May 2013 and August 2014. Data from eight patients with OI and 24 healthy controls were compared using conventional and tissue Doppler echocardiography (TDE). Results:The OI group had significantly lower peak early mitral valve flow velocity (P = 0.027), peak a-wave reversal in the pulmonary vein (P = 0.030) and peak early diastolic velocity of the mitral valve and upper septum (P = 0.001 each). The peak late diastolic velocities of the mitral valve (P = 0.002) and the upper septum (P = 0.037) were significantly higher in the OI group; however, the peak early/late diastolic velocity ratios of the mitral valve (P = 0.002) and upper septum (P = 0.001) were significantly lower. Left ventricular dimensions and aortic and pulmonary artery diameters were larger in the OI group when indexed for body surface area. Both groups had normal systolic cardiac function. Conclusion: Children with OI had normal systolic cardiac function. However, changes in myocardial tissue Doppler velocities were suggestive of early diastolic cardiac dysfunction. They also had increased left ventricular dimensions and greater vessel diameters. These findings indicate the need for early and detailed structural and functional echocardiographic assessment and follow-up of young patients with OI.